Peran Teknologi Informasi, Sumber Daya Manusia Dan Komunikasi Terhadap Implementasi Enterprise Information System (EIS) - Hindra, Firdaus; Hapzi Ali (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The role of Information Technology, Human Resources and Communication in the implementation of Enterprise Information Systems (EIS) is a scientific literature review article within the scope of the field of science. The purpose of this scientific article is to build the role of hypotheses between variables that have been used in further research. Research objects on Google Scholar, Mendeley, journals and other academic literature analysis. The research method uses the research library sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) The role of Information Technology influences the Implementation of Enterprise Information Systems (EIS); 2) The role of Human Resources influences the Implementation of the Enterprise Information System (EIS); and 3) The role of communication influences the implementation of the Enterprise Information System (EIS).